2017
DOI: 10.2196/jmir.7002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Social Processes in Online Health Communities on Patient Empowerment in Relationship With the Physician: Emergence of Functional and Dysfunctional Empowerment

Abstract: BackgroundSubstantial research demonstrates the importance of online health communities (OHCs) for patient empowerment, although the impact on the patient-physician relationship is understudied. Patient empowerment also occurs in relationship with the physician, but studies of OHCs mostly disregard this. The question also remains about the nature and consequences of this empowerment, as it might be based on the limited validity of some information in OHCs.ObjectiveThe main purpose of this study was to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 59 publications
1
53
0
Order By: Relevance
“…In a large survey among the Israeli general population, higher eHealth literacy score was associated with a more extensive interaction and a more balanced power position vis-à-vis with the treating physician [ 22 ]. While eHealth literacy had a direct positive influence on productive functional behaviors in all domains of patient empowerment among members of a Slovenian online health community, it also had a moderating effect on both dysfunctional and functional behaviors [ 65 ]. Using the Health Literacy Questionnaire, a survey on a large Dutch online panel of health care users demonstrated positive relationship between information appraisal, a higher-order health literacy skill, and shared decision making [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a large survey among the Israeli general population, higher eHealth literacy score was associated with a more extensive interaction and a more balanced power position vis-à-vis with the treating physician [ 22 ]. While eHealth literacy had a direct positive influence on productive functional behaviors in all domains of patient empowerment among members of a Slovenian online health community, it also had a moderating effect on both dysfunctional and functional behaviors [ 65 ]. Using the Health Literacy Questionnaire, a survey on a large Dutch online panel of health care users demonstrated positive relationship between information appraisal, a higher-order health literacy skill, and shared decision making [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing the multidimensional determinants of the patient–physician interaction, a recent line of research aimed to establish patient profiles characterized by various skill levels and attitudes, including eHealth literacy [ 32 , 65 , 69 ]. In a large multicountry survey, 4 distinct patient decision styles were described.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, individual literacy and social support are two important OHC features [ 8 ]. In recent years, OHC research has increasingly begun to emphasize relationship-building [ 9 ] and psychological empowerment [ 10 ]. Although these studies have revealed various interesting findings, the factors that govern the patient continuance use of OHCs remain unknown [ 3 ].…”
Section: Methodsmentioning
confidence: 99%
“…Sarah et al [16] proposed that physicians are required to actively communicate with patients in OHCs to improve patients’ satisfaction. Petrič et al [17] found that social process, such as communication in OHCs, can affect the relationship between patients and physicians. In general, physician-patient communication in OHCs can help improve treatment efficiency, as physicians can better serve patients if hospital congestions can be alleviated and medical resources can be redistributed and reused through OHCs.…”
Section: Introductionmentioning
confidence: 99%